Determining factors of the quality of basic education in the public network in Brazil (Research, Society and Development, 2022)
This conceptual paper intends to contribute to the debate about the determinants of the quality of Brazilian basic education. Therefore, it presents a review of three bodies of research: structure of the Brazilian basic education, the financing of public education, and the management of resources allocated to it. In the study on the structure of Brazilian basic education, a statistical design different from that used in the current literature is proposed to capture the effect of the collaboration regime that, as provided by law, takes place between states and their respective municipalities. The study on public financing of basic education and the management of resources allocated to it shows that, on the one hand, the results of Brazilian students in international tests on learning levels remain worse than those of comparable countries and that, on the other hand, there are signs that there is no shortage of public resources for education. Additionally, the school census reports that more than 73% of students at compulsory school age are enrolled in the public education system, which makes the management of resources destined for public education a key element in improving the provision of quality education to Brazilian students. However, the specialized literature demonstrates a divergence on the subject, highlighting the need for further studies on the subject.